PROTECTION OF MSMES AT THE BENGKEL MARKET IN SERDANG BEDAGAI REGENCY REGARDING THE CONSTRUCTION OF THE MEDAN-TEBING TINGGI TRANS SUMATRA TOLL ROAD, A PUBLIC PERSPECTIVE - Harahap, Andli Arya; Ramadhan, Muhammad (Journal Analytica Islamica, 2025)
The construction of the Trans-Sumatra Toll Road Medan-Tebing Tinggi segment, as part of Indonesia's national strategic infrastructure agenda, has had a significant impact on the sustainability of micro, small, and medium enterprises (MSMEs) around Pasar Bengkel, Serdang Bedagai Regency. Although intended to improve connectivity and logistics efficiency, the project has indirectly diverted traffic from local roads that previously served as vital economic arteries for local entrepreneurs. This study aims to analyze the impact of toll road development on MSMEs through the lens of maslahah within the framework of Islamic economic law. Using a normative-empirical legal research method, data were obtained through literature review, document analysis, and interviews with affected MSME actors. Findings show that MSMEs in the culinary and automotive service sectors have experienced declining revenues, workforce reductions, and even business closures. The maslahah analysis identifies three main dimensions of protection: dharuriyyat (safeguarding livelihoods), hajiyyat (ensuring business access), and tahsiniyyat (improving business quality). Local government policies have not been responsive and lack a long-term strategic approach. This study recommends maximizing the integration of MSMEs into rest areas and optimizing digital platforms.